Capital-Budgeting Decisions Involving Combinations of Risky Investments - Van Horne, James (Management Science, 1966)
In this paper, a method is proposed for evaluating combinations of investments when the cash flows are not known with certainty. Various probability concepts are employed; and combinations are evaluated according to their incremental contribution of expected net-present value and variance to the firm as a whole. It is shown that existing investment projects must be considered if the total risk of a particular combination of investment proposals is to be evaluated realistically. Through diversification of investments, a firm is able to obtain the most desirable combination of expected net-present value and risk.